Análise da organização e das condições de trabalho em uma unidade de alimentação e nutrição em relação ao desempenho e à satisfação no trabalho: um estudo de caso - Araújo, Elenice Maria Gonçalves de (2010)
This study aimed to analyze a feeding unit work organization and evaluate environmental conditions of a hospital‟s feeding unit, regarding its influence on employee‟s performance and satisfaction. Relevant subjects such as Feeding an Nutrition Units working conditions, ergology, labor and work organization were approached in the theoretical framework. This is a descriptive research , developed as a study case with an ethnographic approach, using as data research methods, the documentary inventories, observation, validating meetings, data analysis and individual semi-structured interviews, which were conducted in a Hospital‟s foodservice department which serves an average of 4333 meals per month. The selected groups were: cooks, kitchen assistants and kitchen maids. It has been realized the complexity evolving a Feeding Unity service, which requires from its employees efforts to make their best and often renormalizing the prescribed work, thus, mobilizing different values, knowledge and experiences, since each individual brings an unique baggage, which is revealed in the dialogue with other activities. Research results led us to understand the studied organization and to a proper observation of its working conditions. It also indicated that a major restructuring in the department is necessary, especially in its tools and equipments, workload management, physical space and other initiatives that could improve employee‟s satisfaction and performance, considering that staff work needs to be developed as a team. In conclusion, labor can cause satisfaction, personal growth and self-worth booster. However, when environmental conditions and work organization are inadequate, dissatisfaction and frustration tends to appear, and labor ceases to be a favorable element for human life